196k views
5 votes
Р

с
о
1.
Convert the following equation to standard form: y = -3x + 2
— у = 2
3х + y = 2
о 3х + y = -2
о — 3 — у. = 2
ОО
в

User Pierpy
by
5.4k points

1 Answer

0 votes

9514 1404 393

Answer:

3x +y = 2

Explanation:

Standard form is ...

ax +by = c

where a, b, c are mutually prime integers and the leading coefficient is positive.

We can put the equation in this form by adding 3x to both sides.

y = -3x +2

3x +y = 2 . . . . . add 3x to both sides. This is standard form.

User Somebodysomewhere
by
4.8k points